Clinical Outcomes of Autologous Serum Eye Drops in Treating Corneal Ulceration in a Domestic Cat: A Case Base Study - Eka Putri, Rahmi; Hilmi, Mulkiah; Rahmi, Ulfa; Zamzami, Rumi Sahara; Etriwati, Etriwati; Erwin, Erwin; Sugito, Sugito; Syah, Nada Yulian; Ferdian, Riyan; Sari, Wahyu Eka; Safitri, Jessica Anggun (Universitas Syiah Kuala, 2025)
Corneal ulceration is a frequent ophthalmic disorder in domestic cats that can cause ocular discomfort, visual impairment, and serious complications if left untreated. Conventional medical management often provides limited support for epithelial regeneration, leading to the need for alternative therapeutic options. This case study reports the clinical outcome of using autologous serum eye drops (ASEDs) in the treatment of corneal ulceration in a domestic cat. A cat presented with severe epiphora, conjunctival hyperemia, and a centrally located corneal ulcer confirmed by fluorescein staining. Autologous serum was prepared by weekly collection of 6 mL of blood from the dorsalis antebrachii vein, followed by centrifugation and aliquoting into sterile eye drop bottles stored at 4 C. The serum was applied topically twice daily, accompanied by supportive therapy consisting of vitamin A supplementation, multivitamin injections, and an Elizabethan collar to prevent self-trauma. Clinical scoring (03) was used to monitor epiphora, conjunctival hyperemia, and corneal opacity over the treatment period. Marked improvement was observed within 14 days: epiphora and conjunctival hyperemia resolved completely, while corneal opacity improved from moderate to mild, with fluorescein staining becoming negative, indicating complete epithelial closure. No adverse effects were recorded during therapy. This case highlights the potential of autologous serum eye drops as a safe and effective adjunct treatment for feline corneal ulceration, warranting further investigation in larger cohorts to establish standardized protocols for veterinary ophthalmology